2010
DOI: 10.1227/01.neu.0000371990.86656.e8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Care and Survival in a Retrospective Analysis of 1059 Patients With Glioblastoma Multiforme Treated Between 2002 and 2007

Abstract: OBJECTIVE:To investigate the pattern of care and outcomes for newly diagnosed glioblastoma in Italy and compare our results with the previous Italian Patterns of Care study to determine whether significant changes occurred in clinical practice during the past 10 years. METHODS: Clinical, pathological, therapeutic, and survival data regarding 1059 patients treated in 18 radiotherapy centers between 2002 and 2007 were collected and retrospectively reviewed. RESULTS: Most patients underwent both computed tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
39
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 16 publications
11
39
1
2
Order By: Relevance
“…In a comparison between two large series of GB patients collected over subsequent periods (633 cases, 1997-2001; 1059 cases, 2002-2007) by the Italian Patterns of Care Study Group on Gliomas, improved survival results were significantly related to the adoption of 3D-CRT vs. outdated techniques ( p < .001). This corresponds to the same signifi cance level of the introduction of TMZ chemotherapy [ 4 ]. However, the overall survival results remained poor (median survival: 9.5 months; 1-, 2-, and 5-year survival, respectively: 62.3, 24.8, and 3.9 %) in this report as well as in previous and subsequent similar studies [ 5 , 6 ].…”
supporting
confidence: 84%
“…In a comparison between two large series of GB patients collected over subsequent periods (633 cases, 1997-2001; 1059 cases, 2002-2007) by the Italian Patterns of Care Study Group on Gliomas, improved survival results were significantly related to the adoption of 3D-CRT vs. outdated techniques ( p < .001). This corresponds to the same signifi cance level of the introduction of TMZ chemotherapy [ 4 ]. However, the overall survival results remained poor (median survival: 9.5 months; 1-, 2-, and 5-year survival, respectively: 62.3, 24.8, and 3.9 %) in this report as well as in previous and subsequent similar studies [ 5 , 6 ].…”
supporting
confidence: 84%
“…Mexican (16) 1987-1994 16 20 Chinese (13) 1999- 2004 12 17 Korean (2) 1999- 2004 11 20 Italian (17) 2002- 2007 9 25 French (18) 2004- 2006 9 12 Scottish (19) 2004-2009 15 19 Singaporean (present study) 2002-2011 15 24 in local populations and environments mean that these models and calculators need to be validated locally before they can be employed. (19) The present study has shown that the prognostic factors in our local population are similar to those reported worldwide.…”
Section: Discussionmentioning
confidence: 84%
“…(2,13,(15)(16)(17)(18)(19) Earlier studies reporting outcomes during the pre-temozolomide era tend to show poorer survival outcomes when compared to recent studies that were conducted during the chemotherapy era. While our study includes the period before and after data from Stupp's seminal trial was published in 2005, most of our patients had received adjuvant concurrent temozolomide chemotherapy, which likely accounted for their better survival outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma, the most common form of primary malignant brain tumor, is nearly always fatal (1). Although neurosurgeons may be able to remove the main tumor mass, this procedure typically leaves behind a small population of tumor cells that retain the capacity for tumorigenesis (2).…”
Section: Introductionmentioning
confidence: 99%